Advances in peroxide‐initiated graft modification of thermoplastic biopolyesters by reactive extrusion. (29th March 2021) - Tiwary, Praphulla; Najafi, Naqi; Kontopoulou, Marianna
Abstract: We report recent advances in the solvent‐free reactive extrusion of thermoplastic biopolyesters, in the presence of peroxide initiators and tri‐functional cross‐linking/ chain extending agents. The resulting compounds have improved processability and properties compared to the starting materials, including higher melt strength due to long‐chain branching, higher crystallinity, faster crystallization kinetics, and improved mechanical properties. We demonstrate that these strategies are effective in thermoplastic biopolyesters, such as poly(lactide) (PLA) and various poly(hydroxyalkanoates) (PHAs), including poly(hydroxybutyrate) (PHB), and medium‐chain length PHAs. In addition to the improvements in properties, this approach has significant benefits in polymer processing operations, including blend compatibilization, and foaming. We also demonstrate that crosslinked PLA particles prepared by reactive extrusion using peroxide and a tri‐functional coagent, serve as very effective nucleating additives, resulting in crystallization half‐times as low as 1 min, and heat deflection temperature as high as 140°C. These modifications do not have adverse effects on the hydrolytic degradation characteristics of PLA.